A feasibility randomised controlled trial of a fibromyalgia self‐management programme in a community setting with a nested qualitative study (FALCON): Study protocol. (5th September 2020) - Pearson, Jennifer; Coggins, Jessica; Lenguerrand, Erik; Derham, Sandi; Russell, Julie; Walsh, Nicola E.; Cramp, Fiona
Abstract: Background: Fibromyalgia (FM) is a complex long‐term condition associated with chronic widespread pain, fatigue, sleep problems, memory and concentration difficulties and irritable bowel syndrome. Current guidelines for the treatment of FM recommend nonpharmacological interventions. The Fibromyalgia Self‐Management Programme (FSMP) is a nonpharmacological, multidisciplinary exercise and education group intervention. It aims to provide education and teach core skills, enabling those affected by FM to self‐manage. The FSMP is currently codelivered by a multidisciplinary team within a secondary care service. The aim of this feasibility randomised controlled trial (RCT) is to determine the practicality and acceptability of delivering the FSMP in a community setting, informing a future RCT of effectiveness. Methods: The feasibility RCT aims to recruit 70 people with FM. Participants will be randomised to either a community FSMP or control arm. All participants will be asked to complete six patient‐reported outcome measures and one health economics questionnaire on three occasions; baseline, 6 weeks (end of the intervention) and 6 months. Between 12 and 16 participants and four therapists delivering the FSMP will be invited to take part in a semi‐structured interview to explore their experiences of the FSMP. Patient participants will be purposively selected based upon key characteristics. Analysis: Quantitative data will be analysed descriptively to summarise recruitment and attendance, participant reported outcomes and health economic data. Semi‐structured interviews will be transcribed, anonymised and inductively coded. The codes will be grouped into categories and theoretically thematically analysed, comparing the results to existing literature. Trial registration: The trial is registered with ISRCTN registry and was assigned on 29th of April 2020. The registration number is ISRCTN10824225.